Analisis Faktor-Faktor Yang Memengaruhi Fraud Pengadaan Barang dan Jasa Studi Kasus Pada Pemerintah Daerah Kabupaten Cianjur - Zyah Syahira Mubarok; Darya Setia Nugraha; Yanti Rufaedah (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Fraud is an action that is very determental and can affect the sustainability of the economy. Procurement of goods and services is the largest sector for fraud case in Indonesia, especially in corruption case. Procurement of goods and services becomes an occasion for fraudster to commit fraud. Fraud on the procurement of goods and services begins with planning and budgeting. This research was conducted on the factors that led to the occurance of corruption, especially in the procurement of goods and services. The research are use with qualitative analysis. The qualitative analysis is carried out by descriptive, type of research, where this research describes a phenomenon by describing the variables with research problem. The object of this research is the Regional Government of Cianjur Regency which aims to determine the factors that influence fraud in the procurement of goods/services. Data collection techniques are applied in the form of interviews to predetermined data source. The data analysis techniques used by research were data reduction, data display, data analysis, conclusion, and verification. The result of the research conducted showed that arrogance, opportunity, competence, and rationalization did not affected the existence of fraud in the procurement of goods/services in Regional Government of Cianjur Regency. Meanwhile, pressure affects the occurance of human errors in the procurement of goods/services for Regional Government of Cianjur Regency.